Remote Anatomic Pathology Medical Student Education in Washington State: An Early COVID-19 Experience. Issue 5 (20th August 2020) - Parker, Elizabeth U; Chang, Oliver; Koch, Lisa
Abstract: Objectives: The coronavirus disease 2019 pandemic has halted in-person medical student education in many large academic centers, including the University of Washington. We identified a unique opportunity to bring comprehensive and targeted anatomic pathology training to large numbers of medical students who would not receive it otherwise but also need credited coursework. Methods: We developed a comprehensive 2-week remote-learning course encompassing lectures, virtual slides, discussion groups, and unique case-based activities. Activities are tailored to the nonpathologist future clinician, emphasizing basic microscopy and pathology terminology. We employ multiple strategies and technologies to increase engagement while distance learning, including screen annotation, "flipped classroom" slide presentations, and repetition of common themes. Results: Given 13 virtual courses to choose between 13% of students enrolled in our course (70 of our 540 rising third- and fourth-year students), a nearly 10-fold increase in average pathology rotators. Conclusions: This is an unprecedented opportunity to provide tailored anatomic pathology instruction, both helping our medical students continue training during crisis and illuminating the field of pathology for our future colleagues. Preliminary results have been overwhelmingly positive regarding understanding of pathology concepts as well as attitudes toward pathology.